Field of science and scientific criteria of social knowledge P. Bourdieu - Saiganova, Veronica S. (Journal of the Belarusian State University. Philosophy and Psychology, 2019)
In the article the main ideas of P. Bourdieu about the specifics of the social sciences, the conditions for the development of science, the limits of scientific knowledge are considered. The specificity of rationalistic historicism as a strategy of social cognition is revealed. The significance of the concepts of «field of science», «strategy», «historization», «objectivation» and «habitus» in the functioning of the social sciences is shown. The possibility of determining the scientific criteria of social knowledge is analyzed. Objectivation of the subject of objectivation helps the scientist to master the incorporated history of his own discipline and gives the possibility to escape the relativism of social sciences. Social sciences can use their own intellectual tools as reflexive instruments to protect themselves from the influence of the studied social causes.
Keywords: habitus; historization; objectivation; the field of science; social sciences; relativism; strategy